Analisis Faktor Lingkungan Terhadap Kejadian Tuberkulosis (TB) Paru di Wilayah Kerja Puskesmas Blang Bintang Kabupaten Aceh Besar Tahun 2026 - Alif Lia Rinzani; Farrah Fahdhienie; Nopa Arlianti (Pelantar Press, 2026)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. This disease is influenced by unhealthy home environments. Between 2023 and 2025, 23 cases of pulmonary TB were found in the Blang Bintang Community Health Center's work area, with one death and two cases not taking anti-tuberculosis drugs. This indicates problematic TB management in the area. This study aims to analyze environmental factors affecting the incidence of pulmonary TB in the Blang Bintang Community Health Center's work area.This study was conducted using a descriptive analytical method with a case-control design. The case population in this study were 15 respondents with pulmonary TB and the control population in this study were neighbors of pulmonary TB patients who did not suffer from pulmonary TB in the working area of the Blang Bintang Community Health Center, totaling 30 respondents. The sampling technique in this study was total sampling. Data collection was conducted from January 19 to February 5, 2026 using questionnaires and observations. Bivariate data analysis used the chi-square test and multivariate analysis used the logistic regression test.The results of the study showed that there was a significant relationship between temperature p-value 0,001 OR = 21,000 (2,431-181,411), humidity p-value 0,003 OR = 9,750 (1,857-51,188), lighting p-value 0,000 OR = 17,875 (3,284-97,301) on the incidence of pulmonary TB and there was no relationship between floor type, wall type and ventilation area with the incidence of pulmonary TB with a p- value 0,05. Based on the results of the multivariate analysis test using logistic regression, it showed that of the 4 variables tested, namely temperature, humidity, wall type and lighting, the variable that was most at risk of pulmonary TB was the lighting variable with a p-value of 0,003 OR = 42,993 (3,540-522,101).It is hoped that the Blang Bintang Community Health Center will be able to conduct home visits to each community's home, especially to identify home lighting to prevent the occurrence of pulmonary TB